2020
DOI: 10.1186/s12864-020-07149-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic paralogy and function of retinal determination network homologs in arachnids

Abstract: Background Arachnids are important components of cave ecosystems and display many examples of troglomorphisms, such as blindness, depigmentation, and elongate appendages. Little is known about how the eyes of arachnids are specified genetically, let alone the mechanisms for eye reduction and loss in troglomorphic arachnids. Additionally, duplication of Retinal Determination Gene Network (RDGN) homologs in spiders has convoluted functional inferences extrapolated from single-copy homologs in pan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 124 publications
3
18
0
1
Order By: Relevance
“…A previous comprehensive analysis of homeobox genes by Leite et al. (2018) showed that the retention of duplicates is systemic in two arachnopulmonate lineages (spiders and scorpions), an inference subsequently supported by the first whip spider developmental transcriptomes ( Gainett and Sharma 2020 ; Gainett et al. 2020 ) and by embryonic gene expression data ( Gainett and Sharma 2020 ; Nolan et al.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous comprehensive analysis of homeobox genes by Leite et al. (2018) showed that the retention of duplicates is systemic in two arachnopulmonate lineages (spiders and scorpions), an inference subsequently supported by the first whip spider developmental transcriptomes ( Gainett and Sharma 2020 ; Gainett et al. 2020 ) and by embryonic gene expression data ( Gainett and Sharma 2020 ; Nolan et al.…”
Section: Resultsmentioning
confidence: 90%
“…The systemic duplication of developmental patterning genes and gene expression patterns together constitute a highly complex character that unites Arachnopulmonata ( Leite et al. 2016 ; Gainett and Sharma 2020 ; Gainett et al. 2020 ; Nolan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Through manual annotation, we separately examined the genome for evidence of duplicates in genes with known arachnopulmonate-specific paralogs and distinguishable embryonic gene expression patterns, focusing on four leg patterning genes (dachshund (Battelle et al, 2016), homothorax (Gong et al, 2019), extradenticle (Schwager et al, 2017), spineless (Setton et al, 2017)) and the retinal determination gene network (sine oculis, Optix, orthodenticle (Gainett et al, 2020;Samadi, Schmid, & Eriksson, 2015;Schomburg et al, 2015)). All of these genes, known to exhibit arachnopulmonate-specific duplications and spatiotemporal subdivision of expression patterns, were discovered as single-copy in the harvestman genome (Table S2).…”
Section: The Genome Of P Opilio Reveals the Absence Of Arachnopulmonmentioning
confidence: 99%
“…Another peculiarity of Archegozetes is that these mites lack eyes (see more details below). Eye loss has been documented in other arachnid clades, including independently in other members of Acari (Evans 1992; Walter and Proctor 1999), and it has been recently demonstrated that a species of whip spider has reduced its eyes by reducing the expression of retinal determination genes that are shared throughout arthropods (Gainett et al 2020). We sought to determine if eye loss in Archegozetes also is associated with the reduced expression of these genes (see also analysis of photoreceptor genes below).…”
Section: Resultsmentioning
confidence: 99%
“…We sought to determine if eye loss in Archegozetes also is associated with the reduced expression of these genes (see also analysis of photoreceptor genes below). The genes, which have been shown to be expressed in the developing eyes of spiders and whip scorpions, include Pax-6, six1/sine oculis (so), eyes absent (eya), Eyegone, Six3/Optix, and atonal (Gainett et al 2020; Samadi et al 2015; Schomburg et al 2015). We also followed the expression of Al-orthodenticle, a gene previously shown to be expressed in the ocular segment of Archegozetes (Telford and Thomas 1998).…”
Section: Resultsmentioning
confidence: 99%